What has eschatology to do with the gospel? An analysis of papal documents on mission ad gentes. Issue 3 (July 2019) - Patterson, Colin
A theology of mission includes consideration of the reasons for the missionary endeavor. An important source for this area of theology is the set of eight papal documents beginning with Pope Benedict XV's Maximum illud with the most recent being Pope Francis's Evangelii gaudium . Beginning with Jesus' proclamation of the gospel, the mission ad gentes has been carried out with the conviction that on its reception depended a hearer's eternal destiny. Such a rationale based on eschatological beliefs has continued into our day, although during the past century there has been some serious questioning of this view. In this article I analyze the seven papal documents on mission for the frequency with which they mention eschatological and non-eschatological reasons for missionary work. Noteworthy trends emerge from this analysis which raise questions about the continuing vigor of the church's mission ad gentes .